The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ajmg.a.38380
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders in psychiatry and their attitudes toward receiving pertinent and incident findings in genomic research

Abstract: Increasingly more psychiatric research studies use whole genome sequencing or whole exome sequencing. Consequently, researchers face difficult questions, such as which genomic findings to return to research participants and how. This study aims to gain more knowledge on the attitudes among potential research participants and health professionals toward receiving pertinent and incidental findings. A cross‐sectional online survey was developed to investigate the attitudes among research participants toward recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…These findings support other studies of stakeholder's perspectives about RoR in genetics research generally (Kleiderman et al, ; Klitzman et al, ; Middleton et al, ). According to studies examining attitudes toward RoR in psychiatric genetics in particular (Sundby et al, ), stakeholders favored the return of both pertinent and incidental findings to individual research participants, mirroring opinions of our researcher respondents. As has been reported for researchers in other fields of genetics, psychiatry researchers in our study pointed out an additional benefit is that RoR incentivizes participation in studies that require very large sample sizes (Klitzman et al, ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These findings support other studies of stakeholder's perspectives about RoR in genetics research generally (Kleiderman et al, ; Klitzman et al, ; Middleton et al, ). According to studies examining attitudes toward RoR in psychiatric genetics in particular (Sundby et al, ), stakeholders favored the return of both pertinent and incidental findings to individual research participants, mirroring opinions of our researcher respondents. As has been reported for researchers in other fields of genetics, psychiatry researchers in our study pointed out an additional benefit is that RoR incentivizes participation in studies that require very large sample sizes (Klitzman et al, ).…”
Section: Discussionmentioning
confidence: 79%
“…Likewise, Sundby et al () found that psychiatric genetics stakeholders (i.e., patients with mental health disorders, their relatives, and clinicians) favor the return of both pertinent (95%) and incidental (91%) findings to research participants (Sundby et al, ), including to parents of child participants and to the children themselves when of legal age (Sundby et al, ). In another study, 97% of patients with a psychiatric disorder and unaffected relatives reported that they would like to be informed of any clinically relevant genomic findings generated in a study (Bui, Anderson, Kassem, & McMahon, ).…”
Section: Introductionmentioning
confidence: 99%
“…While previous literature has consistently reported very high levels of approval for psychiatric genetic research and testing, it has also been shown that individuals have concerns about autonomy, privacy, discrimination, and coping emotionally with test results (e.g., Austin, Smith, & Honer, ; Bui, Anderson, Kassem, & McMahon, ; Coors, ; DeLisi & Bertisch, ; Illes, ; Jones, Scourfield, McCandless, & Craddock, ; Klitzman et al, ; Lawrence & Appelbaum, ; Meiser et al, ; Meiser, Mitchell, McGirr, Van Herten, & Schofield, ; Middleton et al, ; Roberts, Tsungmey, Kim, & Hantke, ; Salm et al, ; Smith, Sapers, Reus, & Freimer, ; Sundby et al, ; Trippitelli, Jamison, Folstein, Bartko, & DePaulo, ; Wilde, Meiser, Mitchell, Hadzi‐Pavlovic, & Schofield, ; Wilhelm et al, ; Yu, Crouch, Jamal, Bamshad, & Tabor, ). It has also been reported that further information about potential positive and negative implications decreases interest in being tested (Illes et al, ; Wilde, Meiser, Mitchell, & Schofield, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that further information about potential positive and negative implications decreases interest in being tested (Illes et al, ; Wilde, Meiser, Mitchell, & Schofield, ). Genetics researchers are the most hesitant to endorse psychiatric genetic testing, followed by psychiatrists, the general population, and patients/relatives (DeLisi & Bertisch, ; Illes, ; Sundby et al, ), an observation which indicates that attitudes toward psychiatric genetic testing are dependent upon background or degree of expert knowledge. Each group may foresee problems and may have insights or perspectives which are not immediately apparent to other groups.…”
Section: Introductionmentioning
confidence: 99%
“…possibility that may occur. It is easy to obtain, and can be of interest to third parties [2] such as family members, insurance companies and employers.Therefore, there is great interest in this information, especially since genetic predisposition has been clearly demonstrated for various diseases such as cardiovascular pathologies [3,4] diabetes [5], late onset Alzheimer [6], schizophrenia [7]…”
mentioning
confidence: 99%